The Control of Nature - McPhee, John A. frey50 (Thorndike, ME G. K. Hall, 1999)
Large Print
Originally published: New York : Farrar, Straus, Giroux, 1989.
74989
Keywords: Environmental protection; Nature -- Effect of human beings on